Efficacy and safety of single-dose intravitreal dexamethasone implant in non-infectious uveitic macular edema: A systematic review and meta-analysis - Fan, Shipei; Shi, Xing-yu; Zhao, Chao-fu; Chen, Zhen; Ying, Jia; Yu, Song-ping; Li, Jun; Li, Xia (Frontiers in Medicine, 2023)
Purpose We conducted a systematic review and meta-analysis to investigate the efficacy and safety of single-dose intravitreal dexamethasone (DEX) implant for treating non-infectious uveitic macular edema (UME). Methods Studies including clinical outcomes of the DEX implant in UME were comprehensively searched in PubMed, Embase, and Cochrane databases for potential studies from inception to July 2022. The primary outcomes were best corrected visual acuity (BCVA) and central macular thickness (CMT) during the follow-up period. Stata 12.0 was used to perform the statistical analyses. Results Six retrospective studies and one prospective investigation involving 201 eyes were ultimately included. Significantly improved BCVA was observed from baseline to 1 month (WMD = −0.15, 95%CI = −0.24, −0.06), 3 months (WMD = −0.22, 95%CI = −0.29, −0.15), and 6 months (WMD = −0.24, 95%CI = −0.35, −0.13), after single-dose DEX implant. When considering CMT, macular thickness of 1 month (WMD = −179.77, 95%CI = −223.45, −136.09), 3 months (WMD = −179.13, 95%CI = −232.63, −125.63), and 6 months (WMD = −140.25, 95%CI = −227.61, −52.88) decreased in comparison with baseline, with statistical significance. Conclusion Based on the current results, this meta-analysis confirmed favorable visual prognosis and anatomical improvement in patients with UME, after receiving the single-dose DEX implant. The most common adverse event is increased intraocular pressure, which could be controlled with topical medications. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022325969.